ChemInform Abstract: Synthetic and Theoretical Approach Towards Spirothiazolidinone Systems. Issue 28 (21st June 2013) - George, Johnson; Singh, Saurabh; Joshi, Rahul; Pardasani, Pushpa; Pardasani, Ramchand T.
Abstract A convenient route for the synthesis of spirothiazolidinones (V) via nucleophilic cyclocondensation of imines (III) with mercaptoacetic acid is given.